CCL2-CCR2 axis promotes metastasis of nasopharyngeal carcinoma by activating ERK1/2-MMP2/9 pathway - Yang, Jing; Lv, Xing; Chen, Jinna; Xie, Changqing; Xia, Weixiong; Jiang, Chen; Zeng, Tingting; Ye, Yanfang; Ke, Liangru; Yu, Yahui; Liang, Hu; Guan, Xin-Yuan; et al. (My University, 2016)
Distant metastasis remains the major failure of nasopharyngeal carcinoma (NPC). In this study, the roles of chemokine C-C motif ligand 2 (CCL2), and its receptor chemokine C-C motif receptor type 2 (CCR2) on NPC metastasis were investigated. Serum CCL2 and CCL2/CCR2 expression level were remarkably increased in NPC patients compared to non-tumor patients by ELISA and IHC analyses. High expressions of CCL2/CCR2 were significantly associated with NPC metastasis and poor overall survival (OS). High expression of CCR2 is an independent adverse prognostic factor of OS and distant metastasis free survival (DMFS). Overexpressions of CCL2 and CCR2 were detected in high-metastatic NPC cell lines. Upregulating CCL2 and CCR2 respectively in low-metastatic NPC cell lines could promote cell migration and invasion, and exogenous CCL2 enhanced the motility in CCR2-overexpressing cells. On the other hand, downregulating CCL2 and CCR2 respectively in high-metastatic NPC cell lines by shRNA could decrease cell migration and invasion. However, exogenous CCL2 could not rescue the weaken ability of motility of CCR2-silencing cells. In nude mouse model, distant metastasis was significantly facilitated in either CCL2-overexpressing or CCR2-overexpressing groups, which was more obvious in CCR2-overexpressing group. Also, distant metastasis was considerably inhibited in either CCL2-silencing or CCR2-silencing groups. Dual overexpression of CCL2/CCR2 could activate extracellular signal-regulated kinase (ERK1/2) signaling pathway, which sequentially induced matrix metalloproteinase (MMP) 2 and 9 upregulations in the downstream. In conclusion, CCL2-CCR2 axis could promote NPC metastasis by activating ERK1/2-MMP2/9 pathway. This study helps to develop novel therapeutic targets for distant metastasis in NPC.